El precedente constitucional contenido en la sentencia 2505-19-EP/21 y su aplicación en las resoluciones No. 17113-2022-00007 y 09113-2022-00002 de la Corte Nacional de Justicia. - Montoya Garcés, Fernando David (2023)
With the advent of the constitutionalist paradigm, jurisprudence became a directly applicable source of law, however, since it´s a subject that has been little dealt with, there are errors in practice to apply it, according to the doctrine of precedent of law. In the present investigation it proposed to carry out a legal study of the theory of precedent to identify the holding of sentence No. 2505-19-EP/21 of the Constitutional Court of Ecuador, to later contrast it is applicability in resolution No. 17113-2022-00007 and 09113-2022-00002 of a National Court of Ecuador, to determinate if in the two cases mentioned above it carried out in accordance with the jurisprudence and doctrine. For this purpose, three methods used: dogmatic. Since the theory of precedent studied; deductive, to analyze sentence 2505-19-EP/21 and abstract the ratio, obiter, and the rule of precedent; and the inductive method, to arrive at conclusions and reflections on the identification of the precedent in the exposed sentences. Thus, as a result, the precedent of the constitutional sentence misapplied, since the ratio decidendi was erroneously identified, and therefore, the holding was erroneously formulated. Thus, concluding that the Chamber of the National Court of Justice in the appeal sentence in cases No. 17113- 2022-00007 and 09113-2022-00002 identified paragraph 31 of the constitutional sentence as alleged ratios, when said paragraph an obiter dictum.